(2x-1)=(x+4)

Simple and best practice solution for (2x-1)=(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)=(x+4) equation:


Simplifying
(2x + -1) = (x + 4)

Reorder the terms:
(-1 + 2x) = (x + 4)

Remove parenthesis around (-1 + 2x)
-1 + 2x = (x + 4)

Reorder the terms:
-1 + 2x = (4 + x)

Remove parenthesis around (4 + x)
-1 + 2x = 4 + x

Solving
-1 + 2x = 4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1 + 2x + -1x = 4 + x + -1x

Combine like terms: 2x + -1x = 1x
-1 + 1x = 4 + x + -1x

Combine like terms: x + -1x = 0
-1 + 1x = 4 + 0
-1 + 1x = 4

Add '1' to each side of the equation.
-1 + 1 + 1x = 4 + 1

Combine like terms: -1 + 1 = 0
0 + 1x = 4 + 1
1x = 4 + 1

Combine like terms: 4 + 1 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| y+3-4y=15 | | X^2+5/x=8 | | 8/1-7/10 | | 4/3m=1*3 | | 2p^2+8p-7=0 | | 1/3(x+3)=2 | | y=-5(1)+3 | | s^2+49=0 | | 2(n-1)+3-2x=7 | | 4n+4(2+2n)=26 | | 6(8-8p)=-6(1+9p) | | 76-A=44 | | 2^4-4*4.6/5 | | (136x+x)(x+64)= | | s^3-343=0 | | X-6=68 | | 2^4-4*4.6/(20/4) | | 7/9-11/60 | | xy^2+xz^2=0 | | 3x+1=8-x/2 | | .6666(6c+4)-(8c-5)=0 | | (25x)^(3/2)-125 | | 1-70n=7(1-10n) | | Z-2.05=1.95 | | x+3x+5=4(x+1) | | Z-2.05=1.85 | | 7(x+5)-52=18 | | -18-T=34 | | -8-x=2(x-4) | | 2/3(6c+4)-(8c-5)=0 | | B-5.6=3.7 | | -23=j-20 |

Equations solver categories